Influence of Work Environment and Organizational Culture on Employee Performance (Case Study at The PT Kualiti Jaya Semarang) - Sutaat Sutaat (ProBisnis : Jurnal Manajemen, 2023)
Business competition is a phenomenon that often occurs in order to develop a company. One of the factors affecting the success rate of the company is employee performance. Efforts to improve employee performance, including paying attention to the work environment and organizational culture. The problem in this study is whether the work environment and organizational culture affect the performance of PT Kualiti Jaya Semarang employees. This study aims to determine the influence of the work environment and organizational culture simultaneously influence the performance of employees at PT Kualiti Jaya Semarang. The sample in this study amounted to 42 employees using the census method. Data collection methods used in research are questionnaire and interview methods. The analysis used in this study used SPSS 21.00, namely multiple linear regression analysis, F test, and t-test. The results of this study illustrate that the work environment has no significant effect on the performance of PT Kualiti Jaya Semarang employees and organizational culture has a positive and significant effect on the performance of PT Kualiti Jaya Semarang employees.